Ljubezen v športu - Pisk, Jernej (Šport (Ljubljana), 2017)
In this paper we show that sport is full of love. This is why sport is so attractive for human being, and why we like sport. To deeper understand what is love we firstly focus on ancient Greek and Latin words for love and their meanings. Different words for love have in common approval of somebody or something. Love is a positive inclination toward loved. In love we experience to be taken over by the loved thing, as we can experience to be taken over by sport. Along with this love is connected with strong emotions and with vulnerability: in sport the tears of joy and of sorrow are nothing rare. In love we feel joy when somebody succeed. Common interests in sport build a friendship love. Nonetheless, the "give-love" (agape) can reveal us the essence of fair play in sport, while the "need-love" (eros) give us motivation to improve ourselves.
Keywords: agape; eros; filozofija; friendship; ljubezen; love; philosophy; prijateljstvo; sport; šport